2009
DOI: 10.1158/1055-9965.epi-09-0344
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Colorectal Cancer in a Safety-Net Health Care System: Access to Care Is Critical and Has Implications for Screening Policy

Abstract: Background: Data on the number of individuals eligible for screening, and rates of screening, are necessary to assess national colorectal cancer screening efforts. Such data are sparse for safety-net health systems. Methods: A retrospective cohort study of individuals ages 50 to 75 served by a safety-net health system in Tarrant County, TX was conducted to determine (a) the size of the potential screen-eligible population ages 50 to 75, (b) the rate of screening over 5 years among individuals ages 54 to 75, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Prior studies suggest the presence of several barriers ranging from fears of discomfort, complications, or the bowel preparation to logistical concerns including difficulty with transportation, language barriers, difficulty with scheduling appointments, or financial concerns. 20-22 Further, these barriers can be exacerbated by system-level factors such as multistep scheduling processes and/or requiring additional preoperative visits, which may exacerbate transportation and financial issues. 10, 13, 14, 20 For example, it is possible the pre-procedure visit implemented at Parkland to increase patient visit adherence may have a paradoxical effect of increasing patient barriers and decreasing diagnostic colonoscopy completion rates.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggest the presence of several barriers ranging from fears of discomfort, complications, or the bowel preparation to logistical concerns including difficulty with transportation, language barriers, difficulty with scheduling appointments, or financial concerns. 20-22 Further, these barriers can be exacerbated by system-level factors such as multistep scheduling processes and/or requiring additional preoperative visits, which may exacerbate transportation and financial issues. 10, 13, 14, 20 For example, it is possible the pre-procedure visit implemented at Parkland to increase patient visit adherence may have a paradoxical effect of increasing patient barriers and decreasing diagnostic colonoscopy completion rates.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, patients who are more prevention-oriented may be both more motivated to follow up abnormal screening tests and more engaged in primary care. Previous research in primary care settings 5,6,28 and the general population 4,8 that have examined predictors of CRC screening have focused primarily on Bprevalent^screening (having ever been screened) and in settings where colonoscopy (which offers 10 years of protection) was the predominant screening modality. These studies showed that PCP visits [4][5][6][7][8] and physician recommendation were strong predictors of prevalent CRC screening (mostly with colonoscopy).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in primary care settings 5,6,28 and the general population 4,8 that have examined predictors of CRC screening have focused primarily on Bprevalent^screening (having ever been screened) and in settings where colonoscopy (which offers 10 years of protection) was the predominant screening modality. These studies showed that PCP visits [4][5][6][7][8] and physician recommendation were strong predictors of prevalent CRC screening (mostly with colonoscopy). 2,6,8 Our study extends prior work by demonstrating an independent association between prior primary care visits and subsequent Bincident^CRC screening, including outreach screening not linked directly to the primary care visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A retrospective cohort study of screening-eligible individuals in a safety-net health system reported 22% being screened in the last 5 years, and significant predictors of screening participation were female gender, Hispanic ethnicity, being between the age of 65-75 years, and having access to care. 23 Marital status is another important predictor of screening according to a large study of approximately 300,000 participants which noted that, compared to non-partnered people, married and unmarried couples were more likely to get CRC screening. 24 …”
Section: Rates and Predictors Of Adherence To Guidelines For Initimentioning
confidence: 99%